Sovereign risk and armed conflict: An event-study for Colombia (2012)
We study the causal effect of recent landmark events of the Colombian armed conflict on the foreign perception of sovereign risk, as measured by the price of the Credit Default Swap (CDS) of Colombian bonds. We construct a Synthetic Control Group to use as the non-conflict counterfactual of the Colombian CDS price and compare its behavior around relevant conflict-event dates with that of the actual (conflict-affected) Colombian CDS. Results suggest that the impact of conflict on the foreign perception of sovereign risk is sizable but rather idiosyncratic, and depends on the political context surrounding each event. © 2012 Copyright Taylor and Francis Group, LLC.